Modul Ajar Pembelajaran Multikultural pada Muatan Sejarah Lokal SMA di Lampung - Sumargono; Risma Margaretha Sinaga (Universitas Veteran Bangun Nusantara, 2025)
This research focuses on developing multicultural learning modules on localhistory content for high school students in Lampung. Through the multiculturallearning teaching module on local history content, it is hoped that it will fostertolerance for ethnic, linguistic, religious, cultural, and socio-economic diversity.The research method used is the research and development (R&D) method,adapted and modified by Borg & Gall. The procedure for work steps in theresearch includes: 1) preliminary study, 2) development of teaching modules, 3)implementation of the use of teaching modules, and 4) product effectivenesstest. Product effectiveness tests are conducted using experimental methods. Theresearch analysis of the effectiveness test results showed that the posttest scoresof the experimental class (using the developed module) were higher than thoseof the control class (using LKS). This statement is supported by data from theSPSS 16 analysis, which shows a significant difference (p = 0.000 < 0.05) betweenthe experimental and control classes after treatment. Because the average valueof the historical empathy attitude test of the experimental class (the groupsubjected to the developed module) = 128 > the average value of the historicalempathy attitude test of the control class (the group subjected to LKS) = 114.48,it can be concluded that the module developed effectively to increase students’historical empathy. The description above demonstrates that the MulticulturalLearning Teaching Module product for Local History Content at SMA Lampung iseffective in increasing students’ historical empathy